2001
DOI: 10.1086/319474
|View full text |Cite
|
Sign up to set email alerts
|

The Flattened, Rotating Molecular Gas Core of Protostellar Jet HH 212

Abstract: The recently discovered protostellar jet known as HH212 is beautifully symmetric, with a series of paired shock knots and bow shocks on either side of the exciting source region, IRAS 05413-0104 (Zinnecker et al. 1998). We present VLA ammonia maps of the IRAS 05413-0104 molecular gas envelope in which the protostellar jet source is embedded. We find that the envelope, with mass of 0.2 M(sun) detected by the interferometer, is flattened perpendicular to the jet axis with a FWHM diameter of 12000 AU and an axis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 22 publications
13
72
6
Order By: Relevance
“…These authors demonstrated the velocity signature to be consistent with a simple jet rotation model. The value is also in the same range as those measured in H 2 emission for HH 212 SK1 by Davis et al (2000), in which the authors point out that the expected jet rotation speed based on the disk rotation measurements of Wiseman et al (2001) is ∼2 km s −1 , thus demonstrating that our measurements are consistent with a jet rotation interpretation. It is also clear from the modeling of Correia et al (2009) that the toroidal velocity may be confused with other kinematic signatures, and so our calculations are broad indications.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These authors demonstrated the velocity signature to be consistent with a simple jet rotation model. The value is also in the same range as those measured in H 2 emission for HH 212 SK1 by Davis et al (2000), in which the authors point out that the expected jet rotation speed based on the disk rotation measurements of Wiseman et al (2001) is ∼2 km s −1 , thus demonstrating that our measurements are consistent with a jet rotation interpretation. It is also clear from the modeling of Correia et al (2009) that the toroidal velocity may be confused with other kinematic signatures, and so our calculations are broad indications.…”
Section: Discussionsupporting
confidence: 83%
“…This was interpreted as such given the agreement with the sense of a radial velocity gradient across the disk of the same system (Wiseman et al 2001). Codella et al (2007) report no sign of jet rotation in the SiO emission near NK1, whereas in the region SK2−SK4 (∼10−14 from source), they find a gradient in a direction contrary to that reported for SK1 by Davis et al (2000).…”
Section: Hh 212 Nk1 and Sk1mentioning
confidence: 53%
See 1 more Smart Citation
“…4) performed with the SubMillimeter Array (SMA; Lee et al 2006Lee et al , 2007aLee et al , 2008, the IRAM Plateau de Bure (PdB) interferometer Cabrit et al 2007Cabrit et al , 2012, and the Atacama Large Millimeter Array (ALMA; see Lee et al 2014;Codella et al 2014a) reveal the inner ±1 −2 = 450−900 AU collimated jet (width 100 AU) close to the protostar. HH 212 is also associated with a flattened rotating envelope in the equator perpendicular to the jet axis observed firstly with the NRAO Very Large Array (VLA) in NH 3 emission by Wiseman et al (2001) on 6000 AU scales. More recent SMA and ALMA observations in the CO isotopologues and HCO + on ∼2000, 800 AU scales indicates that the flattened envelope is rotating and infalling onto the central source, and can therefore be identified as a pseudodisk according to magnetised core collapse models (Lee et al 2006(Lee et al , 2014.…”
Section: Introductionmentioning
confidence: 75%
“…Observationally, many protostellar disks are found to be in Keplerian rotation (e.g., Wiseman et al 2001 and references therein). There are still some observed protostellar disks found to be in non-Keplerian rotation (e.g., Myers et al2000).…”
Section: Physical Properties Of a Disklike Corementioning
confidence: 99%